Ammonium availability and temperature control contributions of ammonia oxidizing bacteria and archaea to nitrification in an agricultural soil. (October 2017) - Ouyang, Yang; Norton, Jeanette M.; Stark, John M.
Abstract: Soil ammonia-oxidizing bacteria and archaea (AOB and AOA) convert ammonium/ammonia to nitrite in the process of nitrification. However, the potentially differential responses of these AO to substrate and temperature and the effects of conventional and organic nitrogen management on these responses remains poorly understood. We determined the response of nitrification to ammonium substrate concentration and temperature using an AOB specific inhibitor to distinguish the contribution of AOB and AOA to nitrification. Soils were sampled from cornfield plots that had been treated for four years with contrasting nitrogen sources: control (no additional N), ammonium sulfate at two rates and compost. Nitrification potential and net rates were stimulated for one month after fertilization with ammonium sulfate compared to relatively lower and stable rates in control and compost treated soils. For soils that had been fertilized with ammonium sulfate, the proportion of nitrification mediated by AOB in slurry assays was over 90% at 1.0 mM but less than 50% at 0.01 mM. Kinetic analysis showed maximum nitrification activity (Vmax ) for AOB ranged from 0.32 to 4.8 mmol N kg −1 d −1 with a half saturation constant (Km ) of 14–160 μM ammonium; parameters were higher for soils from ammonium sulfate treated plots. Vmax and Km for AOA averaged 0.24 mmol N kg −1 d −1 and 4.28 μM ammonium with no effect of field treatment. The proportion of nitrification due to AOA was lowest at 5 °C, increased with temperature, and was near to 100% at 50 °C; optimum temperature was 41 °C for AOA versus 31 °C for AOB. Understanding the kinetic and temperature response of microbes responsible for nitrification may allow ecosystem models to include these populations as dynamic components driving nitrogen flux. Highlights: Field studies show ammonium fertilizer rapidly increased AOB activity but not AOA. AOB have 20× higher Vmax and 40× higher Km compared to AOA kinetic parameters. AOB mediated 90% of nitrification at 1.0 mM ammonium versus <50% at 0.01 mM. Optimum temperature for nitrification was 31 °C for AOB versus 41 °C for AOA. Target ammonia oxidizing bacteria for inhibition immediately after fertilization.